2017
DOI: 10.1080/15592324.2017.1414121
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress responses in maize are diminished byPiriformospora indica

Abstract: As an endophytic fungus of Sebacinales, Piriformospora indica promotes plant growth and resistance to abiotic stress, including drought. Colonization of maize roots promoted the leaf size, root length and number of tap roots. Under drought stress, the maize seedlings profited from the presence of the fungus and performed visibly better than the uncolonized controls. To identify genes and biological processes involved in growth promotion and drought tolerance conferred by P. indica, the root transcriptome of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Stimulation of jasmonates and JA-responsive genes by A. brassicae infection was strongly inhibited when the plants are colonized by P. indica ( Vahabi et al, 2013 , 2018 ), suggesting that the colonized plants suppress the host immunity because these plants are stronger and healthier and require less JA-dependent defense for protection. In maize seedlings, the drought stress responses were also diminished by P. indica , but in this study, the fungus stimulated the expression of SA-related genes in roots ( Zhang et al, 2018 ). Altered phytohormone levels can also result in a secondary effect: e.g., P. indica stimulated the expression of a tau-type glutathione S -transferase in Chinese cabbage.…”
Section: Sa and Ja Two Phytohormones Involved In Quite Different Defmentioning
confidence: 57%
See 1 more Smart Citation
“…Stimulation of jasmonates and JA-responsive genes by A. brassicae infection was strongly inhibited when the plants are colonized by P. indica ( Vahabi et al, 2013 , 2018 ), suggesting that the colonized plants suppress the host immunity because these plants are stronger and healthier and require less JA-dependent defense for protection. In maize seedlings, the drought stress responses were also diminished by P. indica , but in this study, the fungus stimulated the expression of SA-related genes in roots ( Zhang et al, 2018 ). Altered phytohormone levels can also result in a secondary effect: e.g., P. indica stimulated the expression of a tau-type glutathione S -transferase in Chinese cabbage.…”
Section: Sa and Ja Two Phytohormones Involved In Quite Different Defmentioning
confidence: 57%
“…The information on the involvement of CK in the colonization of the roots by P. indica as well as systemic signal transfer is mainly descriptive. P. indica targeted CK-responsive genes in local root tissues and systemic leaves of colonized plants have been identified in several plant species (e.g., Vadassery et al, 2008 ; Johnson et al, 2014 ; Zhang et al, 2018 ). Vadassery et al (2008) demonstrated that trans -zeatin biosynthesis and the receptor combination CERK1/AHK2 are important for P. indica -mediated growth promotion in Arabidopsis seedlings, while mutants lacking cis -zeatin showed a wild-type response to the fungus.…”
Section: Cytokinin (Ck)mentioning
confidence: 99%
“…Serendipita indica has been praised for its positive effects on a wide variety of plants, including enhanced growth, biomass and yield of agricultural, horticultural and medicinal plants ( Varma et al, 1999 ; Barazani et al, 2005 ; Achatz et al, 2010 ), increased resistance/tolerance to (a)biotic stresses ( Waller et al, 2005 ; Sherameti et al, 2008 ; Rabiey et al, 2015 ; Zhang et al, 2018 ), stimulated adventitious root formation in cuttings ( Druege et al, 2007 ), and improved hardening and acclimatization of micropropagated plantlets ( Das et al, 2017 ). Plants in soil- and agar-based experimental systems have been reported to react to Serendipita inoculation already prior to the establishment of a symbiotic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the early biotrophic stage of S. indica colonization is followed by a programmed cell death-associated later stage ( Lahrmann and Zuccaro, 2012 ). This later stage might be accompanied by SA accumulation, and SA-regulated genes are induced by S. indica under drought stress ( Zhang et al, 2018a ). This difference during late stages of colonization might explain the better performance of S. indica -inoculated plants under lead stress, since an alleviative effect of SA has been shown when wheat seedlings were treated with 200 mg/L lead ( Song et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%